Understanding for whom, under what conditions and how smoking cessation services for pregnant women in the United Kingdom work-a rapid realist review - Claire Tatton; Jenny Lloyd (BMC, 2023)
Abstract Background Maternal smoking in pregnancy is associated with several adverse maternal and infant health outcomes including increased risk of miscarriage, stillbirth, low birth weight, preterm birth, and asthma. Progress to reduce rates of smoking at time of delivery in England have been slow and over the last decade, less than half of pregnant women who accessed services went onto report having quit. This realist review was undertaken to improve the understanding of how smoking cessation services in pregnancy work and to understand the heterogeneity of outcomes observed. Methods The initial programme theory was developed using the National Centre for Smoking Cession and Training Standard Treatment Programme for Pregnant Women and the National Institute for Health and Care Excellence guidance on treating tobacco dependency. A search strategy and inclusion criteria were developed. Four databases were searched to identify published papers and four websites were hand searched to identify any unpublished literature that could contribute to theory building. Realist logic was applied to the analysis of papers to identify the contexts in which the intended behaviour change mechanism(s) were triggered, or not, and towards what outcomes to develop context mechanism outcome configurations. Results The review included 33 papers. The analysis produced 19 context mechanism outcome configurations structured under five closely interconnected domains (i) articulating harm, (ii) promoting support, (iii) managing cravings, (iv) maintaining commitment and (v) building self-efficacy. This review identifies two key processes involved in how services achieve their effects: how material resources are implemented and relationships. Of the two key processes identified, more existing literature was available evidencing how material resources are implemented. However, the review provides some evidence that non-judgemental and supportive relationships with healthcare workers where regular contact is provided can play an important role in interrupting the social cues and social practice of smoking, even where those around women continue to smoke. Conclusions This review clarifies the range of interconnected and bi-directional relationships between services and the personal and social factors in women's lives. It underscores the importance of aligning efforts across the models five domains to strengthen services' ability to achieve smoking cessation.